Synthesis, characterization and solution properties of amphiphilic N-isopropylacrylamide-poly(ethylene glycol)-dodecyl methacrylate thermosensitive polymers - Vieira, NAB; Neto, JR; Tiera, M. J. (Elsevier B.V., 2005)
Terpolymers of N-isopropylacrylamide, dodecyl methacrylate (DOMA) and poly(ethylene glycol) (PEG) methacrylate, were synthesized by random copolymerization, and the composition was controlled to achieve systems having different thermosensitivities. H-1 NMR spectra and gel permeation chromatography (GPC) were employed to characterize the different samples obtained. The solution properties were studied by employing spectrophotometry, fluorescence, and dynamic light scattering techniques. The chemical compositions in the final terpolymers are close to those in the feed. The polymers exhibited cloud point temperatures (T-es) varying from 17 to 52 degrees C. Micropolarity studies using I-1/I-3 ratio of the vibronic bands of pyrene show the formation of amphiphilic aggregates capable of incorporating hydrophobic drugs as the polymer concentration is increased. The critical aggregation concentration (CAC) increases from 3.6 x 10(-3) to 1 x 10(-2) g/l with the PEG content varying from 5 to 35 mol%. Anisotropy measurements confirm the results obtained by pyrene fluorescence and show that the aggregates resulting from intermolecular interactions present different organizations. The hydrodynamic diameters (Dh) of the aggregates determined by dynamic light scattering (DLS) vary from 40 to 150 nm depending on the terpolymer composition. The T-cs and Dh values decreased with the ionic strength, and this behavior was attributed to the dehydration of the polymeric micelles. The capacity of solubilization of the aggregates was evaluated by employing pyrene, and the obtained results confirm the ability to incorporate hydrophobic molecules. (c) 2005 Elsevier B.V All rights reserved.
Keywords: thermosensitive; N-isopropylacrylamide; terpolymers; Polyethylene glycol; nanoparticles